KOMPETENSI PROFESIONAL GURU SENI BUDAYA DALAM MENGIMPLEMENTASIKAN KURIKULUM 2013 (STUDI KASUS GURU TARI DALAM PERENCANAAN DAN PELAKSANAAN PEMBELAJARAN DI SMA JAKARTA BARAT) - Falihatul Ibriza Purnidya Anugrah, - (2021)
ABSTRACT This thesis is entitled about the Professional Competence of Cultural Arts Teachers in Implementing the 2013 Curriculum (Case Study of Dance Teachers in Planning and Implementation of Cultural Arts Learning at West Jakarta High School). This study uses a qualitative approach, with the method of obtaining data from observations, interviews, and documentation studies of a dance teacher at SMA Negeri 33 Jakarta. The data analysis technique used triangulation. The results of this study describe that as a professional teacher, you must have the competence to be able to apply various learning methods, develop and use various tools, media and relevant learning resources. He is also able to organize and implement learning programs, evaluate student learning outcomes, and cultivate the personality of students. From the results of the study, it was concluded that the dance teacher at SMA Negeri 33 Jakarta already had the criteria as a professional teacher, with indications: (1) Having a Learning Implementation Plan (RPP), syllabus, prota and prosem in accordance with the demands of the 2013 curriculum. what he did during the Covid-19 pandemic adjusted the methods and learning media according to the material to be taught. (2) Have the ability to manage dance classes that are maximum and optimal. (3) The ability to evaluate which can be seen from the evaluation of learning conducted every meeting, and evaluation of written and practical tests when the delivery of the material has been completed. (4) The obstacles encountered in this study were resolved through the Subject Teachers' Deliberation (MGMP) activities. In addition, maximum efforts are made by optimizing wiraga, wirama and wirasa training for students to maximize learning outcomes. Keywords: Professional Competence, 2013 Curriculum Implementation, Planning, Implementation and Evaluation